Evaluación agronómica de líneas mutantes de arroz con tolerancia a Pyricularia grisea (ING) - Madriz Muñoz, Jorge; Brenes, Abdenago; Salazar, Rafael; Campos, Rónald; Rivera, Carlos; Fernández, Leonel (Uniciencia, 1996)
Using mutation breeding procedures, CRUZ et al. (1992) obtained 53 rice plants, from a M2 population of 80.000 individuals, which showed tolerance to Pyricularia grisea. The original material came from the commercial cultivar CR-1113, susceptible to this disease. We used in this work a group of 52 lines obtained by the mentioned authors. In the first part of the research 14 lines were selected. Seven of them were promisourius because of their good agronomic performance including the Pyricularia response. The other seven were selected because of their earlyness and desirable agronomic traits. In the second part of this research, the selected lines were multiplied and evaluated in field trials. Results confirmed the expression of the desirable characteristics showed in each group.